PENENTUAN STATUS DAYA DUKUNG LAHAN DALAM PENYERAPAN TENAGA KERJA DI DAERAH PERTANIAN SAYURAN DENGAN SISTEM INFORMASI GEOGRAFIS, STUDI KASUS KECAMATAN SAMARANG, GARUT, JAWA BARAT - Baba Barus (Jurnal Ilmu Tanah dan Lingkungan, 2004)
An index for labor absorption capacity of an agricultural cropping system requires worker number from direct activities and non-direct activities in a field The number of workers from direct activities can be generated from landmanagement (ploughing, fertilization, weeding, etc), meanwhile, the number of workers from non-direct activities such as transportation of manure and product, has to include a distance effect. A distance of a farm from a collection point, where agricultural facilities distributed, contributes to the number of workers required for carrying such products or fertilizers.To calculate a distant effect to absorption capacity is hampered by difficulty in measuring of farm distance in a field,which implies it is rarely found such proper data in producing a labor absorption capacity. GIS as a spatial technology has the capability to produce such as distance effect. This research demonstrated the use of GIS in producing labor absorption capacity index and map of status labor absorption in Samarang sub-district, where several intensive agricultural activities such as paddy, vegetable and perfume grass crops were found The map could be used to understand indirectly the economic situation of the area. Keywords: Cropping system, distance, GIS, labor absorption capacity, Samarang sub-district